Hand-compression pressure cooker: an innovative variation of an existing technique with two example cases. Issue 5 (October 2021) - Colasurdo, Marco; Gabrieli, Joseph Domenico; Cester, Giacomo; Simonato, Davide; Anglani, Mariagiulia; Causin, Francesco
The pressure cooker technique was originally ideated to obtain wedge-flow conditions during arteriovenous malformation or arteriovenous fistula embolisation. The anti-reflux plug created with coils or glue around the tip of a detachable microcatheter enables a continuous injection with a more in-depth penetration. Here we describe two illustrative cases performed with a variation of the technique that we describe as the hand-compression pressure cooker technique.